Evolution of the patella and patelloid in marsupial mammals - Denyer, Alice L. (PeerJ, 2020)
The musculoskeletal system of marsupial mammals has numerous unusual features beyond the pouch and epipubic bones. One example is the widespread absence or reduction (to a fibrous “patelloid”) of the patella (“kneecap”) sesamoid bone, but prior studies with coarse sampling indicated complex patterns of evolution of this absence or reduction. Here, we conducted an in-depth investigation into the form of the patella of extant marsupial species and used the assembled dataset to reconstruct the likely pattern of evolution of the marsupial patella. Critical assessment of the available literature was followed by examination and imaging of museum specimens, as well as CT scanning and histological examination of dissected wet specimens. Our results, from sampling about 19% of extant marsupial species-level diversity, include new images and descriptions of the fibrocartilaginous patelloid in Thylacinus cynocephalus (the thylacine or “marsupial wolf”) and other marsupials as well as the ossified patella in Notoryctes ‘marsupial moles’, Caenolestes shrew opossums, bandicoots and bilbies. We found novel evidence of an ossified patella in one specimen of Macropus rufogriseus (Bennett’s wallaby), with hints of similar variation in other species. It remains uncertain whether such ossifications are ontogenetic variation, unusual individual variation, pathological or otherwise, but future studies must continue to be conscious of variation in metatherian patellar sesamoid morphology. Our evolutionary reconstructions using our assembled data vary, too, depending on the reconstruction algorithm used. A maximum likelihood algorithm favours ancestral fibrocartilaginous “patelloid” for crown clade Marsupialia and independent origins of ossified patellae in extinct sparassodonts, peramelids, notoryctids and caenolestids. A maximum parsimony algorithm favours ancestral ossified patella for the clade [Marsupialia + sparassodonts] and subsequent reductions into fibrocartilage in didelphids, dasyuromorphs and diprotodonts; but this result changed to agree more with the maximum likelihood results if the character state reconstructions were ordered. Thus, there is substantial homoplasy in marsupial patellae regardless of the evolutionary algorithm adopted. We contend that the most plausible inference, however, is that metatherians independently ossified their patellae at least three times in their evolution. Furthermore, the variability of the patellar state we observed, even within single species (e.g. M. rufogriseus), is fascinating and warrants further investigation, especially as it hints at developmental plasticity that might have been harnessed in marsupial evolution to drive the complex patterns inferred here.